High‐dose sodium‐glucose co‐transporter‐2 inhibitors are superior in type 2 diabetes: A meta‐analysis of randomized clinical trials. Issue 9 (22nd June 2021) - Shi, Fang‐Hong; Li, Hao; Shen, Long; Fu, Jing‐Jing; Ma, Jing; Gu, Zhi‐Chun; Lin, Hou‐Wen
Abstract: Aim: To determine the overall efficacy of high‐ versus low‐dose sodium‐glucose co‐transporter‐2 (SGLT2) inhibitors in patients with type 2 diabetes (T2D). Material and Methods: A literature search using MEDLINE, EMBASE and the Cochrane Library was performed from 1 January 2006 to 23 September 2020. Random effects models were used to calculate mean differences (MDs) and pooled relative risk (RR). Prespecified subgroup analyses for each SGLT2 inhibitor, follow‐up and controls were performed. Leave‐one‐out sensitivity and meta‐regression analyses were conducted. Results: A total of 51 randomized controlled trials involving 23 989 participants (weighted mean age, 58.9 years; men, 58.8%) were eligible for our meta‐analysis. For glycaemic regulation ability, a significant reduction in HbA1c (MD −0.080%, 95% confidence interval [CI] −0.100 to −0.060), fasting plasma glucose (MD −0.227 mmol/L, 95% CI −0.282 to −0.173) and postprandial plasma glucose (MD −0.834 mmol/L, 95% CI −1.268 to −0.400) levels was observed in the high‐dose SGLT2 inhibitor group. Treatment with high‐dose SGLT2 inhibitors enabled easier achievement of the target (HbA1c <7%) than low‐dose SGLT2 inhibitors (RR 1.148, 95% CI 1.104 to 1.193). High‐dose SGLT2 inhibitor‐based treatment resulted in more efficient regulation of body weight and blood pressure (body weight: MD −0.346 kg, 95% CI −0.437 to −0.254; systolic blood pressure: MD −0.583 mmHg, 95% CI −0.903 to −0.263; diastolic blood pressure: MD −0.352 mmHg, 95% CI −0.563 to −0.142). The results were similar in sensitivity analyses. Conclusions: The overall efficacy of SGLT2 inhibitors, mainly canagliflozin, dapagliflozin and empagliflozin, was found to be dose dependent.